Olmesartan Associated Sprue-Like Enteropathy and Colon Perforation - Mahmoud Abdelghany; Luis Gonzalez; John Slater; Christopher Begley (Case Reports in Gastrointestinal Medicine)
We are reporting a unique case of olmesartan associated severe sprue-like enteropathy in a 52-year-old woman who presented to our hospital complaining of severe abdominal pain and nausea. At the emergency department she suffered from a cardiac arrest and was found to have a colon perforation. The patient was treated conservatively without surgical intervention and olmesartan was discontinued. After one month, she had complete resolution of her symptoms.